THE CORRELATION BETWEEN TARSAL CIRCUMFERENCE AND BODY SIZE OF SUMATRAN ELEPHANT (Elephas maximus sumatranus) - , PREEYASHINI ADELYN A/P GNANAPATHY; , Dr. drh Hery Wijayanto, MP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of four subspecies of the Elephas maximus (Asian elephant) is Elephas maximus sumatranus, found in Sumatra Island, Indonesia. There have been no researches correlating one part of the body to others of these elephants in captive. The purpose of this research is to find the correlation between the tarsal circumference and the body size (shoulder height, body length, pelvic width, chest girth and distance between angulus scapulae caudalis and tuber coxae) in adult and juvenile Sumatran elephants (<20 years old). The outcome of this research will aid in predicting body size of Sumatran elephants with the linear regressions derived. The samples of Sumatran elephants were taken from Kebun Binatang Gembira Loka Yogyakarta, Taman Wisata Candi Borobodur, and Taman Safari Indonesia 2 Prigen. The research was conducted by measuring the tarsal circumference, body length, shoulder height, chest girth, width of pelvic, and the distance between angulus scapula caudalis and tuber coxae of 28 adults and 6 juvenile elephants using measuring tape and modified compass. The recorded results were statistically analyzed with Microsoft Excel 2007 software to identify the correlation and linear regression of tarsal circumference with the body size variables. From the recorded results and statistical analysis in adults, strong correlations exist between tarsal circumference and body length with linear regression y=2.2951x+101.15, shoulder height with y=1.7387x+81.352, pelvic width with y=0.8405x+51.615 and chest girth with y=2.8601+96.386. In adults, weak correlations exist with the distance between angulus scapula caudalis and tuber coxae with y=0.8323x + 44.832. In juveniles, correlations are very strong between tarsal circumference and body length with linear regression y=3.1796x-11.802 and shoulder height with y=2.6021x-11.325. Correlations are strong with pelvic width, y=0.9859x+25.39 and distance between angulus scapula caudalis and tuber coxae, y=1.132x+9.4302. Correlations are weak with chest girth with y=1.1796x+189.53.